2019
DOI: 10.1186/s12864-019-6080-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide survey, evolution and expression analysis of PHD finger genes reveal their diverse roles during the development and abiotic stress responses in Brassica rapa L.

Abstract: BackgroundPlant homeodomain (PHD) finger proteins are widely present in all eukaryotes and play important roles in chromatin remodeling and transcriptional regulation. The PHD finger can specifically bind a number of histone modifications as an “epigenome reader”, and mediate the activation or repression of underlying genes. Many PHD finger genes have been characterized in animals, but only few studies were conducted on plant PHD finger genes to this day. Brassica rapa (AA, 2n = 20) is an economically importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 97 publications
0
18
0
Order By: Relevance
“…Many studies have showed that PHD genes are involved in various stress responses [ 30 , 31 , 37 ]. To elucidate the putative function of GhPHDs under different stresses, we first identified the cis -acting elements in the promoter region that respond to stresses and phytohormones.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have showed that PHD genes are involved in various stress responses [ 30 , 31 , 37 ]. To elucidate the putative function of GhPHDs under different stresses, we first identified the cis -acting elements in the promoter region that respond to stresses and phytohormones.…”
Section: Resultsmentioning
confidence: 99%
“…AtVIM1 (Variant in methylation 1) functions in DNA methylation-histone interface to maintain the centromeric heterochromation in Arabidopsis [ 29 ]. In addition, PHD proteins are involved in regulating plant response to abiotic stresses and altering plant growth and development [ 30 , 31 ]. In soybean, six Alfin1-type PHD proteins were identified to respond against salt, cold, drought, and ABA treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies showed that PHD genes are involved in various stress responses [41][42][43]. To elucidate the putative function of GhPHDs under different stresses, we rst identi ed the cis-acting elements in the promoter region that respond to stresses and phytohormones.…”
Section: Cis-acting Element Analysismentioning
confidence: 99%
“…Many studies have showed that PHD genes are involved in various stress responses [30,31,46]. To elucidate the putative function of GhPHDs under different stresses, we rst identi ed the cis-acting elements in the promoter region that respond to stresses and phytohormones.…”
Section: Cis-acting Element Analysismentioning
confidence: 99%
“…AtVIM1 (Variant in methylation 1) functions in DNA methylation-histone interface to maintain the centromeric heterochromation in Arabidopsis [29]. In addition, PHD proteins are involved in regulating plant response to abiotic stresses and altering plant growth and development [30,31]. In soybean, six Al n1-type PHD proteins were identi ed to respond against salt, cold, drought, and ABA treatment.…”
Section: Introductionmentioning
confidence: 99%